2018
DOI: 10.21836/pem20180605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the multi-compound complex in Corticosal® in 177 horses with PPID in a retrospective veterinary questionnaire analysis in Germany

Abstract: Effekte des Wirkstoffkomplexes in Corticosal ® bei 177 Pferden mit PPID E. Schramm et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…One systematic review 17 and 13 additional publications [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] were identified that provided data on the frequency of clinical signs within veterinary-diagnosed PPID cases, which were considered in combination with the outcomes from the panel Delphi consultation to categorise clinical signs by the index of clinical suspicion (Table 5). Generalised or regional hypertrichosis (± delayed/abnormal coat shedding) was the most commonly reported sign across all studies (Figures 1-5).…”
Section: Case Selection For Diagnostic Testing and Pretest Probabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…One systematic review 17 and 13 additional publications [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] were identified that provided data on the frequency of clinical signs within veterinary-diagnosed PPID cases, which were considered in combination with the outcomes from the panel Delphi consultation to categorise clinical signs by the index of clinical suspicion (Table 5). Generalised or regional hypertrichosis (± delayed/abnormal coat shedding) was the most commonly reported sign across all studies (Figures 1-5).…”
Section: Case Selection For Diagnostic Testing and Pretest Probabilitymentioning
confidence: 99%
“…In total, one systematic review, 4 11 publications 20,52,[75][76][77][78][79][80][81][82][83] and two abstracts 22,83 were identified that provided data on the pharmacologic treatments and other treatment/management options (Table S4). A summary of the key recommendations is presented in Table 10.…”
Section: Pharmacological Treatments and Other Treatment/management Op...mentioning
confidence: 99%
See 1 more Smart Citation